Transisi Bisnis Grosir Fashion dari Luring ke Daring di Sebuah Pusat Grosir - Marvel, Dustin; Nazaretti, Giovannio; Handoko, Rudy; Ali, Alavi (Kajian Branding Indonesia, 2025)
This research aims to discuss the factors that drive the transition of businesses from offline to online, by exploring the perceptions of wholesale companies in one of the largest wholesale centers in Southeast Asia in facing the COVID-19 pandemic, changes in government regulations, and the emergence of various online platforms for trading. Apart from that, this paper also highlights the challenges faced by wholesale clothing businesses in the digital era, as well as what opportunities there are for wholesale clothing businesses in the digital market. This research was conducted by adopting an approach inspired by the creation of a framework by Donlevy and Zott discussing the benefits obtained from utilizing virtual markets. Even though the research carried out was in line with previous research, various new findings were obtained which were adapted to the focus of the research topic. Therefore, researchers innovated by developing a new framework that was adapted from the basis of the previous framework with additional research results obtained through in-depth interviews from the informants. This research also produced typologies that show each characteristic, perception and behavior of business people at the Tanah Abang Metro Wholesale Center.